EVALUASI PENGGUNAAN OKSIGEN SEBAGAI PENGHASIL UAP TERAPI NEBULIZER PADA PASIEN ASMA - Santosa, Agus; ., Endiyono (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
In regional hospitals are still found nebulizer therapy using oxygen as a as a driving gas, but there is already a tool Jet nebulizer is intended specifically for producing steam therapy for asthma patients. This study aims to evaluate the effectiveness of oxygen as a driving gas for nebulisers steam therapy in asthmatic patients. This study is an observational analytic study. Popolation in this study was asthma patients who received nebulizer therapy by using oxygen as a driving gas, the number of samples in this study amounted to 30 respondents. The measured variables were Breath Pattern, Respiration Rate (RR), Breath Sound, Oxygen Saturation (SpO2). The results showed that, the nebulizer using oxygen as a driving gas is still effective against changes in breath patterns from fast and shallow (Tachypne) to become normal (Eupnea). Nebulizer using oxygen as a driving gas is still effective for lowering RR of asthma patients. Nebulizer using oxygen as a driving gas is still effective against changes in breath sound from rhonchi / wheezing to vesicular. Nebulizer using oxygen as a driving gas is still effective against the increase in blood spO2 in asthmatic patients. The conclusions of this study are nebulizer therapy by using oxygen as a driving gas, still effective a changes in breath sound from tachypne to eupnea , can increase SpO2 in blood and decrease RR, and change breath pattern from rhonchi / wheezing to vesicular. Keywords: Nebulizer, Asthma